2019
DOI: 10.1088/1674-1056/ab50fb
|View full text |Cite
|
Sign up to set email alerts
|

Improving entanglement of assistance by local parity–time symmetric operation*

Abstract: We investigate entanglement of assistance without and with decoherence using a local non-Hermitian operation, i.e., parity–time ( P T ) symmetric operation. First we give the explicit expressions of entanglement of assistance for a general W-like state of a three-qubit system under a local parity–time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In [26] the authors found that the no-signaling principle can be violated when applying a local non-Hermitian operation on one of the entangled particles. More recently, it has also been shown that non-Hermitian operation can be used to suppress the decoherence of an amplitude damping (AD) model [27][28][29][30][31] and slow down the decoherence of the pure phase damping model [32], and so on. Moreover, recent research [33] has shown that the qubit-qubit entanglement can obviously be enhanced by means of either local, prior, or post non-Hermitian operations.…”
Section: Introductionmentioning
confidence: 99%
“…In [26] the authors found that the no-signaling principle can be violated when applying a local non-Hermitian operation on one of the entangled particles. More recently, it has also been shown that non-Hermitian operation can be used to suppress the decoherence of an amplitude damping (AD) model [27][28][29][30][31] and slow down the decoherence of the pure phase damping model [32], and so on. Moreover, recent research [33] has shown that the qubit-qubit entanglement can obviously be enhanced by means of either local, prior, or post non-Hermitian operations.…”
Section: Introductionmentioning
confidence: 99%
“…At present, non-Hermitian systems attract a great deal of interest, which is no longer only of academic interest since it is becoming experimentally accessible in the optical system [23,24]. Meanwhile, the study of non-Hermitian systems was generalized to various fields [25][26][27][28][29][30][31][32]. Results of these above research show that the non-Hermitian approach has powerful functions on the control of the quantum system and its quantum state.…”
Section: Introductionmentioning
confidence: 99%
“…In [31], the authors found that the no-signalling principle can be violated when applying the local non-Hermitian operation on one of the entangled particles. More recently, it has also been shown that non-Hermitian operation can be used to suppress the decoherence of amplitude damping model [32][33][34][35][36], and slow down the decoherence of pure phase damping model [37], and so on. Moreover, recent research [38] has shown that the qubit-qubit entanglement can obviously be enhanced by the means of either local prior or post non-Hermitian operations.…”
Section: Introductionmentioning
confidence: 99%